2011
DOI: 10.1111/j.1365-263x.2011.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐marsupialization as an alternative treatment for mucocele in pediatric dentistry

Abstract: Micro-marsupialization can be used to treat mucoceles in paediatric dentistry. It is simpler to perform, minimally invasive, requires no local infiltration of anaesthesia, has a lower postoperative complications rate, and is well-tolerated by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 17 publications
1
24
0
5
Order By: Relevance
“…The variation in color depends on the size of the lesion, its proximity to the mucosal surface, and the elasticity of the overlying tissue. [1121316] In our study, around 30% of the cases had bluish appearance, and almost all of them were more than 1 cm in size.…”
Section: Discussionsupporting
confidence: 47%
“…The variation in color depends on the size of the lesion, its proximity to the mucosal surface, and the elasticity of the overlying tissue. [1121316] In our study, around 30% of the cases had bluish appearance, and almost all of them were more than 1 cm in size.…”
Section: Discussionsupporting
confidence: 47%
“…Micromarsupialisation has been proved to be a simple, relatively noninvasive, painless, effective, and low recurrence technique to treat oral ranulas and selected mucoceles by Amaral et al (2012) and Sagari et al (2012) wherein all cases showed complete healing within 30 days after the procedure [8, 11]. However, these surgery procedures have several disadvantages such as trauma, pain, lip disfigurement, damage to adjacent vital structures, and ducts leading to development of satellite lesions and can also be expensive to the patient [12, 13]. Therefore, we have undertaken a nonsurgical treatment protocol with highly potent corticosteroids (betamethasone).…”
Section: Discussionmentioning
confidence: 99%
“…Her parents reported, during the first months of life, the spontaneous formation of a pink oblong vesicle in the left internal part of the lower lip ( Figure 1 ). The color [ 13 ], the localization [ 14 ], and the shape [ 15 ] have been considered coherent with a mucocele lesion; however, a conclusive diagnosis requires histopathological examination. As spontaneous regression of these oral lesions has been reported [ 16 ], the parents planned only a further control.…”
Section: Case Reportmentioning
confidence: 99%